Design of Wideband Complex Ratio Measuring Unit (CRMU) in multilayer microstrip-slot technology for the application of QPSK modulator - Abdul Rahim, Sharul Kamal (2012)
This article presents the design of a planar complex ratio measuring unit (CRMU) for the designated frequency range of 2 to 6 GHz in multilayer microstrip-slot technology. This CRMU utilizes one in-phase power divider and three 3 dB quadrature couplers. The analysis is performed to assess the performance of CRMU for the purpose of Quadrature Phase Shift Keying (QPSK) modulation. The parameter of transmission coefficients, return losses, q-point circle centers and QPSK constellations are presented. CST Microwave Studio is used for the CRMU design and the analysis on S-parameter performances is performed using Agilent's Advanced Design System (ADS) software.